ANALISIS PENGARUH SISTEM ENROLLMENT TERHADAP KEPUASAN NASABAH DARI TABUNGAN DAN ASURANSI PEGAWAI NEGERI (TASPEN) DALAM PENARIKAN GAJI PADA PT BANK SYARIAH INDONESIA (BSI) KC BUKITTINGGI GURU HAMZAH - Rahmadhani Rahmadhani; Novera Martilova (Jurnal Ekonomi dan Bisnis, 2023)
The results of this study conclude that the Enrollment System has a significant influence on customer satisfaction at BSI KC Bukittinggi as evidenced by the results of a simple linear regression Y = 12.368 + 0.531 X1 where this figure shows a positive value. The results of the t test obtained a significant value of tcount > ttable or 2.659 > 1.746, so it can be concluded that H0 is rejected H1 is accepted, which means that the Enrollment System Variable (X) partially influences Customer Satisfaction Variable (Y). In the sense that the better the Enrollment System service at BSI KC Bukittinggi, the higher customer satisfaction will be at BSI KC Bukittinggi. The result of the coefficient of determination (R2) of 30.7% has a weak effect because the value does not reach 50% while the remaining 69.3% is influenced by other variables that are not included in the research that the author is doing. These findings indicate that the Enrollment System service is one of the factors that determine the increase in customer satisfaction at BSI KC Bukittinggi Guru Hamzah.